Activin A Reduces GIRK Current to Excite Dentate Gyrus Granule Cells - Zheng, Fang; Valero-Aracama, Maria Jesus; Schaefer, Natascha; Alzheimer, Christian (Frontiers in Cellular Neuroscience, 2022)
Activin A, a member of the TGF-β family, is recognized as a multifunctional protein in the adult brain with a particular impact on neuronal circuits associated with cogni-tive and affective functions. Activin receptor signaling in mouse hippocampus is strongly enhanced by the exploration of an enriched environment (EE), a behavioral paradigm known to improve the performance in learning and memory tasks and to ameliorate depression-like behaviors. To interrogate the relationship between EE, activin signaling and cellular excitability in the hippocampus, we performed ex vivo whole-cell recordings from dentate gyrus granule cells (GCs) of wild type mice and transgenic mice expressing a dominant-negative mutant of activin receptor IB (dnActRIB), which disrupts activin signaling in a forebrain-specific fashion. We found that, after overnight EE housing, GC excitability was strongly enhanced in an activin-dependent fashion. Moreover, the effect of EE on GC firing was mimicked by pre-treatment of hippocampal slices from control mice with recombinant activin A for several hours. The excitatory effect of activin A was preserved when canonical SMAD-dependent signaling was pharmacologically suppressed, but was blocked by inhibitors of ERK-MAPK and PKA signaling. The involvement of a non-genomic signaling cascade was supported by the fact that the excitatory effect of activin A was already achieved within minutes of application. With respect to the ionic mech-anism underlying the increase in intrinsic excitability, voltage-clamp recordings re-vealed that activin A induced an apparent inward current, which resulted from the suppression of a standing G protein-gated inwardly rectifying K+ (GIRK) current. The link between EE, enhanced activin signaling and inhibition of GIRK current was strengthened by the following findings: (i) The specific GIRK channel blocker ter-tiapin Q occluded the characteristic electrophysiological effects of activin A in both current- and voltage-clamp recordings. (ii) The outward current evoked by the GIRK channel activator adenosine was significantly reduced by preceding EE exploration as well as by recombinant activin A in control slices. In conclusion, our study identi-fies GIRK current suppression via non-canonical activin signaling as a mechanism that might at least in part contribute to the beneficial effects of EE on cognitive per-formance and affective behavior.